Tailoring the electroluminescence of a single microwire based heterojunction diode using Ag nanowires deposition. Issue 12 (5th March 2020) - Wu, Yuting; Xu, Juan; Jiang, Mingming; Zhou, Xiangbo; Wan, Peng; Kan, Caixia
Abstract : A single Ga-doped ZnO microwire covered by Ag nanowires (AgNWs@ZnO:Ga MW) was utilized to construct a promising ultraviolet light source, with p-GaN serving as a hole injection layer. Abstract : The collective oscillation of conduction electrons at the interface between metallic nanostructures and semiconductors has become one of the most attractive approaches to facilitate the luminous efficiency of light-emitting materials and devices. In this work, a single Ga-doped ZnO microwire covered by Ag nanowires (AgNWs@ZnO:Ga MW) was utilized to construct a promising ultraviolet light source, with p-GaN serving as a hole injection layer. In addition to substantially enhancing the light output, the electroluminescence (EL) features also illustrated that the dominating peak wavelength of the heterojunction diode was centered around 375.0 nm, accompanied by spectral linewidth narrowing to around 10 nm, suggesting that radiative recombination was primarily distributed in the single ZnO:Ga MW in the diode operation. The modulation of the emission features by the Ag nanowires, especially the typical near-band-edge (NBE) emission dominating the heterojunction diode, can be assigned to the near-perfect matching between the AgNWs-plasmons and the ZnO:Ga excitons, leading to the radiation recombination rate of the electron–hole in the ZnO:Ga MW channel being faster than the others. Therefore, the proposed strategy of incorporating ultraviolet plasmonic metallic nanostructures can be utilized to construct high-performance optoelectronic devices in the short wavelength spectral region.